Approaching the Easter Theme in Early Childhood Education: Analysis of Lesson Plans by Pre-Service ECE Teachers During Practicum - Koulouridi, Maria; Σιάτρας Αναστάσιος (Greek Journal of Religious Education (GjRE), 2025)
This study explores how future kindergarten teachers develop Easter lesson plans during their practical training. We analyzed 312 activities from 184 student teachers using thematic analysis. Our findings revealed a strong emphasis on social and emotional development and communication, with language and visual arts being prominent. However, STEM subjects and physical education were notably underrepresented, suggesting students’ limited familiarity with these areas. We also observed significant use of digital media. This research enhances our understanding of the pedagogical approaches future kindergarten teachers employ when creating Easter-themed lesson plans.